La casuistique du baiser - Marianne Blidon (EchoGéo)
The city is classically defined as a space carrying modern values of emancipation and freedom. This paper will highlight the urban public space as normative space. “A kiss is not just a kiss” for same-sex couple in public space. The heterosexuality of the street is an insecure appearance that has to be maintained by regulatory regimes.